2012
DOI: 10.1177/097215091201300210
|View full text |Cite
|
Sign up to set email alerts
|

Tourism Service Quality: A Dimension-specific Assessment of SERVQUAL*

Abstract: In the ever more competitive nature-based tourism market, service providers must maintain every edge to remain competitive. Owing to the customer-oriented service endeavours, tourism enterprises, either private or public, need to improve their service offerings so as to retain or improve their market share. To help service providers identify their strengths and weaknesses, the most widely accepted measurement scale for service quality is the SERVQUAL instrument. One of the criticisms levelled against the SERVQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
14

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 29 publications
2
43
0
14
Order By: Relevance
“…Results have confirmed that out of four tourism service dimensions, Assurance dimension is a significant contributor of overall tourist satisfaction. The present study supports the findings of Bhat (2012) who suggested improvement in Reliability and Responsiveness dimension to improve overall quality of tourism services. Similarly, it is put forwarded that management must pay attention to these two dimensions where the SERVPERF scores are relatively low so as to improve the overall tourist satisfaction and achieve overall tourism competitiveness.…”
Section: Conclusion and Suggestionssupporting
confidence: 91%
“…Results have confirmed that out of four tourism service dimensions, Assurance dimension is a significant contributor of overall tourist satisfaction. The present study supports the findings of Bhat (2012) who suggested improvement in Reliability and Responsiveness dimension to improve overall quality of tourism services. Similarly, it is put forwarded that management must pay attention to these two dimensions where the SERVPERF scores are relatively low so as to improve the overall tourist satisfaction and achieve overall tourism competitiveness.…”
Section: Conclusion and Suggestionssupporting
confidence: 91%
“…The SERVQUAL model has been criticized for not being sufficient to meet service quality measurements needs (see, e.g. in Bhat, 2012). Despite criticism, the model has been widely used and it has been a foundation for development of several measurement tools for service quality in various industries.…”
Section: Customer Satisfaction and Service Qualitymentioning
confidence: 99%
“…In this dimension, it generally looks at a variety of tourism related services, and their quality standards provided by both public and private owned entities at the tourist attractions. Literature reviewed has indicated broad investigation into different themes of service quality in the tourism industry and they include: tourist satisfaction [88,89], human resources [90,91], destination competitiveness [92,93], organizational and financial performance [94,95], and measurement [96,97]. Accordingly, service quality can be evaluated through two broad sub-dimensions: (1) tourism services; and (2) recreation services.…”
Section: Service Qualitymentioning
confidence: 99%